QUALITY OF LIFE IN CHILDREN WITH CHRONIC DIARRHEA - F.F. Zhvaniya; T.S. Lazareva; E.F. Lukushkina; I.V. Vinyarskaya ("Paediatrician" Publishers LLC, 2009)
The results of evaluation of quality of life in children from 1 to 3 years old with chronic diarrhea in exacerbation or remission with QUALIN questionnaire is presented in this article. Authors used two types of questionnaire: doctors' and parents'. Obtained data was compared to indices of healthy children. Proved, that children in early age with chronic diarrhea, as in exacerbation, as in remission, have significantly lower rates of quality of life compared to healthy coevals.Key words: children, quality of life, QUALIN questionnaire, chronic diarrhea.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):16-19)